Magnetic sporopollenin based cyclodextrin and calixarene: Molecular modelling, characterization and application for determination of non-steroidal anti-inflammatory drugs / Syed Fariq Fathullah Syed Yaacob - Syed Fariq Fathullah, Syed Yaacob (2019)
The interaction between β-CD and calixarene with selected non-steroidal anti-inflammatory drugs (NSAIDs), namely, indoprofen (INP), ketoprofen (KTP), ibuprofen (IBP) and fenoprofen (FNP) was investigated using modelling approach. In molecular modelling study, molecular dynamics and AM1 semi-empirical method was used to perform the geometry optimization calculation 1:1 ratio stoichiometry of host and guest molecule complexes. Complexation of host with each selected NSAIDs was investigated at all possible orientation, coordinates and different system. For β-CD host complexation, the most optimum position of each NSAIDs was located at center of β-CD cavity with range energy of -0.02 to -0.37 Hatrees (-13.15 to -230.22 kcal/mol). Most optimum position of selected NSAIDs for calixarene host complexation was situated at outside cavity of calixarene with energy between -0.01 to -0.13 Hatrees (-5.57 to -82.30 kcal/mol). Several hydrogen bonds were measured indicating there are intermolecular forces existed between host and guest molecules. From molecular modelling study, the result showed that there is interaction between NSAIDs with β-CD and calixarene. Therefore, β-CD and calixarene have been chosen as receptor for application of trace analysis of NSAIDs. In experimental approach, β-CD and calixarene framework functionalized bio-polymeric spores of sporopollenin hybrid magnetic materials (MSp-TDI-βCD and MSp-TDI-calix) were synthesized and applied as sorbents of magnetic solid phase extraction (MSPE) for determination of NSAIDs. The structure of MSp-TDI-βCD and MSp-TDI-calix were characterized by Fourier-transform infrared spectroscopy (FTIR), X-Ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-Ray spectroscopy (EDX), Brunauer-Emmett-Teller (BET) analysis and vibrating sample magnetometer (VSM) measurement. In order to develop the extraction performance of synthesized adsorbents, decisive MSPE affective parameters were optimized such as sorbent amount, sample volume, extraction and desorption time, type and amount of organic eluent as well as pH solution prior high performance liquid chromatography (HPLC) determination. The best working conditions for both adsorbents as follow; 10 mg of MSp-TDI-βCD and 30 mg of MSp-TDI-calix, 30 min extraction time, 30 min desorption time for MSp-TDI-βCD and 10 min desorption time for MSp-TDI-calix, 200 mL sample volume, 1.5 mL of acetonitrile and sample solution at pH 4. Under the optimized conditions, the analytical validity of MSPE procedure for both adsorbents was evaluated and the following merits were obtained: linearity over concentration range of 0.5 - 500 μg/L, limits of detection (LOD) from 0.16 - 0.37 μg/L for MSp-TDI-βCD and 0.06 - 0.27 μg/L for MSp-TDI-calix, limits of quantification (LOQ) for MSp-TDI-βCD and MSp-TDI-calix between 0.53 - 1.22 μg/L and 0.20 - 0.89 μg/L, respectively. Excellent precision in terms of reproducibility and repeatability with inter-day (n = 15) and intra-day (n = 5) relative standard deviation were acquired for MSp-TDI-βCD in range of 2.5 - 4.0 and 2.1 - 5.5 respectively and for MSp-TDI-calix between 2.5 - 3.2 and 2.4 - 3.9, respectively. The application of prepared adsorbent MSp-TDI-βCD and MSp-TDI-calix towards environmental real samples on tap water, drinking water and river water was successfully studied. Good percentage recovery was achieved for both adsorbents (92.5 - 123.6% for MSp-TDI-βCD) and (88.1 - 115.8% for MSp-TDI-calix) with acceptable %RSD of 1.9 - 12.4% and 1.6 - 4.6% respectively.